2019
DOI: 10.18705/2311-4495-2019-6-2-12-17
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging of Acute Ischemic Stroke: Current State

Abstract: РезюмеЗа последнее десятилетие отмечается значительное усовершенствование методов нейровизуализации для улучшения ранней диагностики острого инсульта. Компьютерная и магнитно-резонансная томография часто используются при внутримозговом кровоизлиянии или для оценки противопоказаний к тромболизису, чтобы обнаружить локализацию зоны ишемии и оценить время начала инсульта. С наличием быстрых и передовых методов визуализации отмечается растущий интерес к их применению для прогнозирования успеха и исключения рисков … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…It is believed that when discussing the consequences of acute cerebrovascular accident (death, disability, complicated and severe course) is often determined by age, time since the onset of the disease, level of consciousness, severity of stroke, tactics and organization of treatment and diagnostic process [2,3,9,10,12,15]. Of fundamental importance for the organization of care for patients with ACA have works in which it was found that neuroimaging and primary neuroprotective therapy should begin within the "therapeutic window" and that their implementation during this period reduces mortality and disability due to stroke [1,5,8]. At the same time, a number of authors point to the leading role of the nature, location and extent of brain damage [11].…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that when discussing the consequences of acute cerebrovascular accident (death, disability, complicated and severe course) is often determined by age, time since the onset of the disease, level of consciousness, severity of stroke, tactics and organization of treatment and diagnostic process [2,3,9,10,12,15]. Of fundamental importance for the organization of care for patients with ACA have works in which it was found that neuroimaging and primary neuroprotective therapy should begin within the "therapeutic window" and that their implementation during this period reduces mortality and disability due to stroke [1,5,8]. At the same time, a number of authors point to the leading role of the nature, location and extent of brain damage [11].…”
Section: Discussionmentioning
confidence: 99%